Dissemination of false content online in Malaysia: a legal update - Daud, Mahyuddin; Zulhuda, Sonny (2018)
It has been witnessed that the booming of digital technologies had stimulated positive impact towards usage of social media. Although this has been fruitful for the country especially in the age of digital economy, it is also disturbing to note that social media has turned into a ‘nesting ground’ to spread lies and rumours. False content had caused confusion and misunderstanding – especially when public interest is at stake. Some tarnishes the good name of not only country’s leaders but also government officials. Hence, this paper analyses legal framework on regulation of false content online in Malaysia and selected jurisdictions. In particular, two recent initiatives were highlighted (1) introduction of a website – ‘Sebenarnya.my’ designed to verify authenticity of news; and (2) emplacing liability on WhatsApp group administrator to monitor false content. The extent of how far these new initiatives to effectively curb the spread of false content is yet to be seen. In gearing towards a healthier, dynamic and progressive digital society, it should be reminded that proactive measures taken must be balanced with constitutional right to freedom of expression within specified boundaries set by the law.